Effect of Rebozo and Birth Ball Techniques on Length of Active Phase for Primi Maternity Woman at Ayu Independent Practicing Midwife In 2023 - Azhari, Armita Sri; Oktavia, Sesmi Nanda (PT. Riset Press International, 2024)
There are still many problems in Indonesia, including prolonged labor which is one of several causes of maternal and newborn deaths. According to the World Health Organization (WHO), the maternal mortality rate is very high, around 287,000 women died during and after pregnancy and childbirth in 2020. The research aims to determine the effect of the rebozo and birth ball techniques on the length of the active phase in mothers giving birth in primary care. This research is quantitative research with a pre-experimental research design, namely a two-group pre-test-post-test design approach. This research was carried out at the Mandiri Ayu Practical Midwife in 2023. Time of the research was carried out in November 2023 - February 2024. The population in this study was all 2023 primigravida mothers from August-October with a sample of 22 people. The data obtained was normally distributed so we used a parametric test, the dependent T-test. The research results showed that the length of the active phase in the control group without treatment with the Rebozo technique and birth ball in primi mothers was 7.36 with a standard deviation of 0.505 and a std error of 0.152, while in the intervention group given the treatment it was 4.18 with a standard deviation of 0.982 and std error 0.296. The results of statistical tests using the independent t-test with p-value = 0.000 (p≤0.05). The conclusion of the study shows that there are differences between the Rebozo and birth ball techniques the control and intervention groups regarding length of the active phase in primary birth mothers. The researcher's suggestions can be applied midwifery practice accelerating Rebozo and birth ball techniques.